Neuropsychology in literacy action proposed by the Paulo Freire method - Fernandes , Andressa Lis; Paula , Alcimar de; Paula , Cleudia Fernandes da Silva; Silva , Israel Lucas Fernandes de Paula e; Sales, Ricardo José Viana (Seven Editora, 2024)
The present article was proposed with the objective of evaluating, through neuropsychological constructs, cognitive processes and strategies that corroborate the effectiveness of the Paulo Freire method, and there is a concern about the number of students enrolled in the educational program who have given up on their schooling process, since Paulo Feure’s method is available to intervene and reduce the rates of the illiterate contingent. The method was designed to teach literacy and/or facilitate reading and writing in young people and adults. The methodology consists of the correlation between neuropsychological concepts with the Paulo Freire method to verify the reason for its effectiveness through a literature review of authors such as: Abramovay (2015), Catânia (1999), Eysenck (2017), Mendonça (2007), Paulo Freire (1967), going through the practice of the authors of this work, with the objective of understanding and elucidating the cognitive processes and strategies that favored the success of Paulo’s method in the literacy action of adults, with the intention of contributing to the composition of training materials for literacy teachers of Youth and Adult Education (EJA). Therefore, the following were described: Paulo Freire’s sociolinguistic method, the neuropsychological explanation of the learning contained in the method and the importance of these contributions to the continuing education of EJA literacy teachers. Paulo Freire’s method privileges the mnemonic system so that students can be taught to read and write more quickly and fluidly and has in its essence to make the learner an active and participatory being in the construction of his own knowledge, integrating "learning how to do something" with which he "already knows how to do it". It promotes knowledge "about what it already knows how to do" by composing a knowledge continuum in new information, both in terms of "what to do" and "doing", thus weaving a network of practical meanings for knowledge. Many learners know how to "do something" but need to "learn about something they do." The search for PG, already known in sound and its meaning, leaves the iconic and echoic memory free of competing stimuli, contributed to the decoding present in the method, together brings the phonological and orthographic neighborhood, which also privilege memorization; Consequently, it facilitates reading and graphic mastery of the writing of the mother tongue without overloading the attentional system, thus expanding the student’s learning capacity. The task of finding PG in newspapers, magazines, song lyrics, labels and poems by the learners, makes it promote an exploratory process that activates the structure of the visuospatial sketch, both in the Visual Cache and in the Inner Scribe. In this way, the mnemonic capacity is enhanced in an interaction with the associative capacity produced by the central executive. The high level of immediate recall of sentences is substantially beyond the capacity of the phonological loop, however, it can be explained by the proposed capacity of four chunks of the episodic buffer that is activated when the method presents in sentence form within the context in sentences, providing an increase in the mnemonic capacity of the learner, going from 4 to 16 recalled units. which favors learning. DOI:https://doi.org/10.56238/sevened2024.009-042